Pelaksanaan Perjanjian Kerja Sama Pt. Indogreen Jaya Abadi Dalam Penggunaan Lahan Masyarakat Di Desa Sungai Bela Kecamatan Kuindra - Ahmad Sofyan Harahap; Ali Azhar; Vivi Arfiani Siregar (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
This study aims to examine and analyze the implementation of the cooperation agreement between PT. Indogreen Jaya Abadi and the local community regarding land use in Sungai Bela Village, Kuindra Subdistrict, as well as to identify the obstacles encountered in carrying out the agreement. A land-use cooperation agreement between a company and landowning communities constitutes a legal relationship that must fulfill the principles of contract law as regulated under the Indonesian Civil Code, particularly the principles of consensus, balance, and good faith. This research employs an empirical (socio-legal) method with a descriptive qualitative approach, using interviews, observation, and documentation study involving the parties directly engaged in the agreement. The findings indicate that the implementation of the cooperation agreement between PT. Indogreen Jaya Abadi and the community of Sungai Bela Village has generally been carried out in accordance with the terms agreed upon, although several obstacles remain, including delays in compensation payments, unclear land boundaries, and limited community understanding of the agreement's contents. These factors have the potential to trigger disputes if not promptly resolved through deliberation or available legal remedies. This study recommends strengthening legal assistance for the community and enhancing transparency in the implementation of the agreement to achieve a fair and mutually beneficial cooperative relationship between both parties.